Efforts to Legalize the Prostitution Business and Its Relationship with Gender Equality Based on the Perspective of Normative Law and Economics in Indonesia (Universitas Negeri Semarang, 2020)
This article was created to provide a discussion that the legalization of the prostitution business cannot be legalized for the collective benefit of the community from a normative and economic perspective. The choice of the topic of this article is motivated by the author's personal awareness of normative issues in society. In addition, the researcher also tries to prove the consequences of this legalization on the discourse on gender equality and how the main problem of disparity between male-female competencies will not be resolved in this regard. Not only do we need to change the norms in society for this legalization to work, but also how fundamental changes to Indonesian law, such as the Marriage Law, are also needed and certainly require a lot of resources. Interesting discourse circulating in social circles regarding legalizing prostitution that prostitution is an immoral activity, or my body my choice, and claims that legalizing will create a better working environment for prostitutes are some of the elements of this article. Do not forget a study of the validity/absoluteness of a person's right to freedom to choose anything for himself.